2017 European guidelines for the management of genital herpes. (December 2017) - Patel, Rajul; Kennedy, Oliver J; Clarke, Emily; Geretti, Anna; Nilsen, Arvid; Lautenschlager, Stephan; Green, John; Donders, Gilbert; van der Meijden, Willem; Gomberg, Mikhail; Moi, Harald; Foley, Elizabeth
Genital herpes is one of the commonest sexually transmitted infections worldwide. Using the best available evidence, this guideline recommends strategies for diagnosis, management, and follow-up of the condition as well as for minimising transmission. Early recognition and initiation of therapy is key and may reduce the duration of illness or avoid hospitalisation with complications, including urinary retention, meningism, or severe systemic illness. The guideline covers a range of common clinical scenarios, such as recurrent genital herpes, infection during pregnancy, and co-infection with human immunodeficiency virus.